P4_11 Solar Wind - Tilley, Frederick; Davis, Claire; Hague, Pete (Physics Special Topics, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>The physics behind the solar wind is investigated in order to determine whether it is possible to have a star whose solar pressure could be held back by the local interstellar medium, thus placing it in hydrostatic equilibrium with no solar wind. It is found using a simplified model that such a star probably cannot exist.